KAJIAN INDEKS PERTANAMAN DAN POLA TANAM PADA SUBAK SADAP TIRIS DAN SUBAK BUKAN SADAP TIRIS DI DAERAH IRIGASI KEDEWATAN, BALI - Ratna Komala Dewi; I Nyoman Parining (Universitas Udayana, 2019)
This research was conducted to identify the cropping index as well as the cropping pattern in the subak sadap tiris and not sadap tiris in the Kedewatan Irrigation Area, Bali. The location of the study was selected purposively, namely Subak Mambal (subak not tadah tiris, namely subak which obtained irrigation water directly from the dam) and Subak Temaga (subak sadap tiris, is a subak that get irrigation water from their upstream subak). Data were collected through interviews using a structured questionnaire for 60 farmers, namely in each subak as many as 30 farmers were selected randomly and focus group discussions with pekaseh and heads were dropped during the period June to August 2018. To explore cropping indexes and cropping patterns were analyzed qualitatively descriptive. The results showed that cropping index in subak sadap tiris was 250 with rice-rice cropping pattern, while cropping index in subak not sadap tiris was 200-300 with more varied cropping patterns, namely 66.66% rice-rice cropping patterns; 16.67% cropping pattern of rice-rice-flowers/vegetable/corn; 16.67% cropping pattern (rice + flowers/vegetable/corn) - (rice + flowers/vegetable/corn).